KONSTRUKSI PESAN TARI „KECAK‟ PADA MASYARAKAT BADUNG, BALI - Sumiati, Sumiati; Girsang, Lasmery RM (Universitas Bunda Mulia, 2018)
Bali becomes the world‟s tourism that has varied culture, one of them is „Tari Kecak‟ („TariCak‟ or „Fire Dance‟). Different with other dance using music („gamelan‟), „Tari Kecak‟ just uses thedancer‟s sound/shouting like “cak cak ke cak cak ke”as the art. Through qualitative research based onconstructive paradigm, the researcher depended on participative observation and in depth interview tothe key informants and informants (from local society and tourists). By using Semantic Meaning Theoryfrom Charles Osgood, the results show five meanings from „Tari Kecak‟, namely (a) avoiding curse, (b)as a belief system, (c) as a holy thing, (d) as an art and culture and also (e) as economic income.Keywords: Message, Tari Kecak, Semantic Meaning Theory